Detecting and tracking abrupt changes in wireless multipath channels - Sashidharan, V.; Kannu, A. P. (2012 Fourth International Conference on Communication Systems and Networks (COMSNETS 2012), 2012)
We consider wireless multipath channels where abrupt changes may happen in the form of appearance/ disappearance of a new/existing path due to sudden changes in the environment. In this paper, we address the problem of estimating and tracking a channel whose taps may disappear/appear at random times. We employ abrupt change detection algorithms and propose a scheme that uses a Kalman filter in parallel with a change detector. In order to reduce the computational complexity, our change detector is developed such that it operates using the outputs of Kalman filter. Through simulations, we compare the performance of change detector based algorithm with the conventional channel estimation algorithms.